US-China Competition in Artificial Intelligence: Implications on Global Governance (Journal of Asian Development Studies, 2023)
The struggle between the United States and China in artificial intelligence (AI) has the potential to alter the balance of power drastically and has significant ramifications for global governance. The race for technological dominance could begin. The dominating nation in AI may impact world governance by establishing technical norms, forming laws, and limiting access to AI technologies. AI can boost productivity, innovation, and competitiveness through economic growth. As a result, both China and the USA seek to have their economic influence. Geopolitical tensions, ethical issues, technology standards, and data governance may all be impacted. A cooperative and inclusive global governance system that addresses these challenges will be necessary for AI to maximize its potential and lessen its risks. The US is in the lead in the competition in artificial intelligence. Since AI is a worldwide phenomenon, international cooperation is necessary to overcome its problems. Global governance can help governments, organizations, and professionals share knowledge, collaborate, and coordinate to establish best practices and shared research and foster an inclusive and all-encompassing approach to AI development. Under global governance, there are strategies to lessen the possibility of conflicts between these two foes. These include promoting open and transparent government, improving societal understanding, or developing institutions that reduce the likelihood of conflict.